The Use of Pig Manure Fertilizer on the Growth, Production, Protein Content, and TDN of Pakchong Grass - Kaca, I Nyoman; Suariani, Luh; Suwitari, Ni Ketut Etty; Ariawan, I Wayan Eka Putra; Wiratama, I Made Adi (Formosa Journal of Multidisciplinary Research, 2024)
Manure is a fertilizer that comes from a mixture of livestock waste, urine, and leftover livestock feed. Pig manure can be used as fertilizer because it contains Nitrogen, phosphorus and potassium. Solid pig manure contains quite high Nitrogen nutrients of 0.95%, Phosphorus 0.35%, and Potassium 0.40%, so that pig manure is effective as an organic fertilizer that will be beneficial for plant growth. This study aims to see the effect of the use of pig manure fertilizer on the growth, production, nutritional quality and TDN of Pakchong Grass. A Randomized Block Design (RAK) was used with five treatments, namely without the use of pig manure fertilizer (P0), Grass Plants fertilized with 5 tons/ha of pig manure fertilizer (P1), Grass Plants fertilized with 10 tons/ha of pig manure fertilizer (P2), Grass Plants fertilized with 15 tons/ha of pig manure fertilizer (P3), and Grass Plants fertilized with 20 tons/ha of pig manure fertilizer (P4). The results of this study indicate that providing pig manure fertilizer of up to 20 tons/ha can increase the growth, production, quality and TDN of Pakchong Grass.